ANALISIS KEUNTUNGAN PADA USAHATANI PADI SAWAH TADAH HUJAN DAN KONTRIBUSINYA TERHADAP PENDAPATAN RUMAH TANGGA PETANI DI KECAMATAN JANGKAT KABUPATEN MERANGIN - Kernalis, Emy; Lubis, Arsyad; Ulma, Riri Oktari (Jurnal AGRISEP, 2019)
Jangkat District is one of the districts which is the center for producing rice in Merangin Regency. Determination of the research’s location was conducted  purposively, namely Muara Madras Village and Pulau Tengah Village, which are the two villages with the largest rice field planting area in Jangkat District. Sampling in this study using the simple random sampling method or a simple random method in which all of population has the opportunity to be used as a research sample and obtained as many as 57 samples. The purpose of this study were (1) To determine the benefits of lowland rice farming in Jangkat District, Merangin District and (2) to determine the contribution of lowland rice farming to household income of farmers in Jangkat District, Merangin Regency. Profit analysis results show that the average revenue of farmer on rice farming is Rp. 10,749,401/ha. While the average total cost, both real and calculated, is Rp. 8,098,506/ha. So that the average profit obtained from rice farming is Rp. 2,650,895/ha. Contribution of lowland rice farming to household income is only 4.63%. While the contribution of coffee farming revenue was 7.53%, potatoes 69.78%, and chili 18.06%. Which means that rice farming contributes the smallest compared to other farms.